An Investigation of Pre-Service English Teachers’ Self-Efficacy in Web Pedagogical Content Knowledge - Hakkı Bağcı; Cihat Atar (Sakarya University Journal of Education)
The aim of this study is to identify pre-service English teachers’ self-efficacy in web pedagogical content knowledge. The Web Pedagogical Content Knowledge (WPCK) is valuable in comparison to other technology-based models (e.g. TPACK) as it offers a holistic approach by integrating content knowledge with web knowledge specifically rather than focusing on technology in general. The sample of this study consists of 110 pre-service English teachers studying at two state universities in Istanbul and Sakarya, Turkey in the academic year of 2018-2019. The data was collected through “The Scale of Web Pedagogical Content Knowledge” developed by Lee, Tsai and Chang (2008) and adapted into Turkish by Horzum (2011). The data was analyzed through SPSS and the variables university, grade, gender, daily amount of time spent on the internet and social media were considered in addition to identifying participants’ competence levels. The findings demonstrate that the participants have a high level (‘I totally agree’) of self-efficacy in the five sub-dimensions of WPCK. Out of the variables, only grade is observed to have a significant effect while university, gender, daily amount of time spent on the internet and daily amount of time spent on social networks are observed to have a no significant effect on self-efficacy levels. The analysis offers insights into pre-service teachers’ competence and self-efficacy in the use of web for pedagogy, content knowledge, pedagogical knowledge and the integration of them. The findings of this study are expected to contribute to pre-service teacher training and the successful integration of the web into content knowledge for pedagogic purposes.